2013
DOI: 10.1002/humu.22363
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interaction Between SNPs and Microsatellite in the Transcriptional Regulation of Insulin-Like Growth Factor 1

Abstract: A CA-repeat microsatellite in insulin-like growth factor 1 (IGF1) promoter was associated with interindividual variation of circulating IGF1 level. Previously, we reported that such association was due to variation of haplotype unit in a linkage disequilibrium block composed of microsatellite and single-nucleotide polymorphisms (SNPs), suggesting the presence of an interaction between them. In this study, reporter assays were performed to investigate the regulatory effect and interaction of genetic variants on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
(42 reference statements)
2
26
0
Order By: Relevance
“…Our early results were consistent with genetic epidemiological findings and supported a biological basis for the association between the blood concentration of IGF1 and the alleles of the STR in IGF1 promoter2829. Near the transcription starting site, the promoter of IGF1 contains three tagging SNPs and one STR (a CA dinucleotide repeat) within a common haploblock28.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Our early results were consistent with genetic epidemiological findings and supported a biological basis for the association between the blood concentration of IGF1 and the alleles of the STR in IGF1 promoter2829. Near the transcription starting site, the promoter of IGF1 contains three tagging SNPs and one STR (a CA dinucleotide repeat) within a common haploblock28.…”
supporting
confidence: 87%
“…1. For reporter constructs of the common promoter haplotypes (Supplementary Table T1)29, 1.5-kb long fragments of the IGF1 promoter region, ranging from −1491 to −5 relative to the translation start site, were synthesized by PCR using genomic DNA from normal subjects. The fragment was amplified by a forward primer containing a BglII restriction site (underlined) (5′-AGC AGATCT GCCCCAGGATAACACAAAGA-3′) and a reverse primer containing a HindIII restriction site (underlined) (5′-AGC AAGCTT GCTTCTGAAGTACAAAGTCT-3′).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, several authors have also reported that IGF1 and its analogues are associated with an increased death in patients with progressive MM (Standal et al 2002, Chou et al 2012, Wu et al 2014, whereas the administration of metformin results in the reduction of deaths in patients with progressive disease (Wu et al 2014). In fact, Chen et al (2013) recently demonstrated that the IGF1 rs35767 SNP together with two neighbour SNPs constitutes a haplotype that efficiently regulates transcriptional activity (Chen et al 2013). Similarly, several studies have consistently reported that carriers of the IGF1 rs35767T allele showed significantly higher levels of circulating IGF1 than those harbouring the WT allele (Mannino et al 2013, Sesti et al 2014 and that the presence of this variant is associated with an increased risk of developing several types of cancer (Ollberding et al 2012, Qian et al 2014.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…In human, an impact of microsatellite length on transcriptional activity was investigated in the background of haplotypes (rs35767:T > C, the CArepeat microsatellite, rs5742612:T > C, and rs2288377:T > A). As a form of T-(CA-repeat microsatellite)-C-A The (CA) 17 repeat microsatellite with a C-T-T haplotype in the promoter region of the insulin-like growth factor 1 (IGF1) gene showed relatively low transcriptional activity, whereas the (CA) 21 repeat microsatellite with a T-C-A SNP, exhibited high transcriptional activity, suggesting that microsatellite length variation could control gene expression with a neighboring SNP event (Chen et al, 2013). While this study is limited to human genome, it demonstrates that analyses of microsatellite with SNP allow us to understand the genetic variability in dogs.…”
Section: Microsatellite Polymorphism and Snp In Dogsmentioning
confidence: 99%
“…Firstly, microsatellites related to behavior-related genes had a variable repeat size (or number) and affected behavioral characteristics in dog breeds (Takeuchi et al, 2009a(Takeuchi et al, , 2009bKonno et al, 2011), and could also interact with SNPs in the regulation of transcription (Chen et al, 2013). Secondly, VNTRs of the dopaminergic neurotransmitter genes such as DRD4, TH, DBH, and DAT were reviewed in dogs (Hejjas et al, 2007(Hejjas et al, , 2009, and a repeat polymorphism of the TH gene was related to behavioral tests (Kubinyi et al, 2012).…”
Section: Conclusion and Further Remarksmentioning
confidence: 99%